2022
DOI: 10.3390/magnetochemistry9010003
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxides Nanoparticles as Components of Ferroptosis-Inducing Systems: Screening of Potential Candidates

Abstract: This study presents an analysis of a set of iron oxides nanoparticles (NPs) (γ-Fe2O3, α-FeOOH, δ-FeOOH, 5Fe2O3·9H2O, and Fe3O4) as potential candidates for ferroptosis therapy in terms of a phase state, magnetic characteristics, and the release of Fe2+/Fe3+ as ROS mediators. Due to the values of saturation magnetization for Fe3O4 (31.6 emu/g) and γ-Fe2O3 (33.8 emu/g), as well as the surface area of these particles (130 and 123 m2/g), it is possible to consider them as promising magnetically controlled carriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…In previous studies (Dzeranov et al 2022), we have shown that the concentration of iron ions released by magnetite is less than 1% of the total iron concentration, as confirmed by elemental analysis. Therefore, iron ions play a critical role in assessing the This journal is © The Royal Society of Chemistry 20xx…”
Section: Harber-weiss Reactionsupporting
confidence: 75%
“…In previous studies (Dzeranov et al 2022), we have shown that the concentration of iron ions released by magnetite is less than 1% of the total iron concentration, as confirmed by elemental analysis. Therefore, iron ions play a critical role in assessing the This journal is © The Royal Society of Chemistry 20xx…”
Section: Harber-weiss Reactionsupporting
confidence: 75%
“…Comparative evaluated sorption analysis of samples showed that the sorption capacity of M/TAHA-0.5 for ciprofloxacin was more than doubled compared to HA-free MTA, increasing from 1 mg g −1 to approximately 2.5 mg g −1 . 81 Detailed investigation of kinetics, thermodynamics and mechanism of sorption of M/TA under effect of HA is a subject of further experiments.…”
Section: Resultsmentioning
confidence: 99%